2002
DOI: 10.1056/nejmoa020742
|View full text |Cite
|
Sign up to set email alerts
|

Normal Vision despite Narrowing of the Optic Canal in Fibrous Dysplasia

Abstract: Encasement of the optic canal in fibrous dysplasia causes narrowing of the canal, but that in itself does not result in visual loss. Therefore, prophylactic decompression of the optic nerve does not appear to be indicated on the basis of the presence of fibrous dysplasia on diagnostic images alone, since it does not correlate with visual loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
153
2
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 21 publications
0
153
2
6
Order By: Relevance
“…Hypersomatotropinemia in MAS can be associated with significant morbidity due to exacerbation of polyostotic fibrous dysplasia in the presence of elevated GH levels [106,113]. Hypersomatotropinemia has also be implicated in sarcomatous transformation of bone tumors in a MAS patient [114].…”
Section: Molecular Genetics Of Pituitary Tumorsmentioning
confidence: 99%
“…Hypersomatotropinemia in MAS can be associated with significant morbidity due to exacerbation of polyostotic fibrous dysplasia in the presence of elevated GH levels [106,113]. Hypersomatotropinemia has also be implicated in sarcomatous transformation of bone tumors in a MAS patient [114].…”
Section: Molecular Genetics Of Pituitary Tumorsmentioning
confidence: 99%
“…[36][37][38] In a cross-sectional survey of unselected patients with sphenoid and optic canal involvement, Lee et al 39 found no correlation between visual loss and canal stenosis on quantitative radiography. 39 Typically, the mechanisms for the optic neuropathy in fibrous dysplasia patients include acute compression from a secondary mass lesion such as a bone cyst with or without haemorrhage, sphenoid-ethmoid mucocoele, or sarcomatous degeneration. Chronic optic nerve traction may also play a role in some cases.…”
Section: Fibrous Dysplasia and Other Primary Bone Diseasementioning
confidence: 99%
“…precocious puberty and hyperthyroidism) known as the McCune Albright syndrome (MAS) [4,5]. The symptoms associated with FD are well described in the literature, with some series reporting up to one-third of patients having visual complaints, including blurred vision, diplopia, and epiphora [6]. The most devastating consequence of CFD is the loss of vision due to optic nerve compression (ONC).…”
Section: Introductionmentioning
confidence: 99%
“…The most devastating consequence of CFD is the loss of vision due to optic nerve compression (ONC). Although radiological evidence of ONC in CFD is found in 50-90% of the patients [6], the management of these patients is more often based on personal experience and/or expert opinion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation